2016
DOI: 10.4236/oalib.1102777
|View full text |Cite
|
Sign up to set email alerts
|

Survival and Growth of Mangrove Tree Seedlings in Different Types of Substrate on the Ajuruteua Peninsula on the Amazon Coast of Brazil

Abstract: The present study investigated the growth and survival of seedlings of Rhizophora, Avicennia, and Laguncularia raised in three different substrates: mangrove soil, latosol, and sand. The study was based on an entirely random factorial design (3 × 3) × 3, with three tree species, three substrates, and three replicates. The experiment was conducted in a nursery installed in the municipality of Bragança, in the northern Brazilian state of Pará. The seedlings were grown in 17 cm × 27 cm polyethylene containers. Su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…The combination of 75% Mud and 25% Sand forms an excellent substrate. The results obtained are similar to those of Costa et al [2016] who examined the growth and survival of Rhizophora spp., Avicennia and Laguncularia seedlings on three different types of substrates in nursery on the coast of Brazil. Dewiyanti et al…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The combination of 75% Mud and 25% Sand forms an excellent substrate. The results obtained are similar to those of Costa et al [2016] who examined the growth and survival of Rhizophora spp., Avicennia and Laguncularia seedlings on three different types of substrates in nursery on the coast of Brazil. Dewiyanti et al…”
Section: Discussionsupporting
confidence: 87%
“…The substrates used were mangrove mud and fine sand extracted in situ [Costa et al, 2016]. The use process involved quantitative mix of mangrove sand and mud from three combinations: • a substrate mix of 75% sand and 25% mud; • a substrate mix of 50% sand and 50% mud; • a substrate mix of 25% sand and 75% mud.…”
Section: Experience 1: Substrate Preparation and Seedlings Raisementioning
confidence: 99%
“…Machangulo Peninsula, Maputo province) as having a high potential for mangrove forests occurrence. Although, this region is currently dominated by sand dunes (Bandeira and Paula, 2014) and coastal lakes and lagoons (da Costa and Ribeiro, 2017), other studies performed in the Amazon Coast of Brazil (see Costa et al, 2016) revealed a high rate of survival and growth of mangrove seedling survival on sandy soils. Excluding estuaries, coastal Mozambique has rather sandy sediments; the sand dunes dominating the long stretch of southern Mozambique, and also South Africa (Kwazulu/Natal) (Tinley, 1985) are potentially favourable for mangrove recolonization provided that a conducive condition exists, such as regular tidal flooding (Spier et al 2016).…”
Section: Suitable Areas For the Occurrence Of Mangrove Speciesmentioning
confidence: 98%
“…In addition, some mangrove areas have also been degraded due to the exploitation of the wood by the local fishers population. However, many of these areas have been replanted through the programs of mangrove rehabilitation on the Ajuruteua Peninsula (see Lopes et al 2013;Costa et al 2016;Fernandes et al 2018).…”
Section: Introductionmentioning
confidence: 99%